2016
DOI: 10.1002/mus.25263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ATP and adenosine on contraction amplitude of rat soleus muscle at different temperatures

Abstract: ATP is involved in both pre- and postsynaptic regulation of rat soleus muscle contractility, and these processes are significantly more pronounced at low temperatures. Muscle Nerve 55: 417-423, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 48 publications
(112 reference statements)
1
18
1
1
Order By: Relevance
“…In this study, we have shown that in contrast to rat soleus muscle where contractility increases at low temperatures, rat and mouse EDL demonstrate a decrease in the amplitude of muscle contractions induced either by electric stimulation of the nerve or carbachol application under hyothermia. Interestingly, suramin, a non‐selective antagonist of P2 receptors, but not 8‐ p SPT, a non‐selective antagonist of adenosine receptors, fully prevented the decrease of EDL contractility at low temperatures similarly to its inhibitory action on hypothermia‐induced increase of contractility in the rat soleus muscle . We hypothesize that the hypothermia‐dependent decrease of ES‐induced contractions of the EDL muscle might be due to a negative feedback mechanism provided by endogenous ATP via presynaptic P2Y receptors since suramin completely blocks that mechanism and prevents the hypothermic decrease in contractility.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…In this study, we have shown that in contrast to rat soleus muscle where contractility increases at low temperatures, rat and mouse EDL demonstrate a decrease in the amplitude of muscle contractions induced either by electric stimulation of the nerve or carbachol application under hyothermia. Interestingly, suramin, a non‐selective antagonist of P2 receptors, but not 8‐ p SPT, a non‐selective antagonist of adenosine receptors, fully prevented the decrease of EDL contractility at low temperatures similarly to its inhibitory action on hypothermia‐induced increase of contractility in the rat soleus muscle . We hypothesize that the hypothermia‐dependent decrease of ES‐induced contractions of the EDL muscle might be due to a negative feedback mechanism provided by endogenous ATP via presynaptic P2Y receptors since suramin completely blocks that mechanism and prevents the hypothermic decrease in contractility.…”
Section: Discussionmentioning
confidence: 73%
“…For example, in the frog sartorius muscle, agonists of P2Y receptors inhibited acetylcholine release at the presynaptic level and that effect became more prominent at hypothermic temperatures than that at physiological conditions . In the rat soleus muscle similar P2Y receptor‐mediated presynaptic inhibition of acetylcholine release was significant at physiological temperatures, but gradually diminished with a decrease of bath temperature . At the postsynaptic level, ATP at normothermia did not affect carbacholine‐induced contractions of rat soleus muscles, but under hypothermic conditions such contractions became significantly higher in the presence of ATP .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations